High resolution wireless body area network with statistically synchronized sensor data for tracking pulse wave velocity - Li, Kejia; Warren, Steven (IEEE, 2013)
Wireless body area networks (WBANs) will take on more diverse forms in terms of their sensor combinations and communication protocols as their presence is extended to a greater number of monitoring scenarios. This paper presents an application layer protocol that solves issues caused by sensor nodes that must compete for high speed, real-time communication with the receiver. Such applications emphasize the delivery of large amounts of raw data from different sensor nodes in a time-synchronized manner, rather than channels that experience intermittent operation. An example of tracking pulse wave velocity (PWV) is introduced in this paper, where high-precision PWVs are estimated with the help of timeline recovery and feature extraction processes in MATLAB.
Keywords: Photoplethysmogram; Pulse wave velocity; Statistical synchronization; Wireless body area network